Introduction to Islamic banking and finance - Kettell, Brian (Wiley, 2011)
Introduction to Islamic Banking and Finance is a succinct guide to the key characteristics of Islamic banking highlighting how these differ from conventional banking. This detailed book illustrates how Islamic banking is consistent with the Sharia'a, a key element of which is the prohibition on collecting and paying interest. This central religious precept appears to rule out most aspects of modern finance but it does allow money to be used for trading tangible assets and business, which can then generate a profit. Brian Kettell's book looks at all aspects of Islamic banking, including chapters on its creation and evolution through to detailed discussions of the issues involved in the Sharia'a contracts of Murabaha, Mudaraba, Musharaka, Ijara, Istisna'a, and Salam. Islamic insurance (Takaful) is also covered. Finally the book takes a look at Sharia'a law and Sharia'a boards, indicating the roles and responsibilities that come with membership.